Trade Costs, 1870–2000 - Jacks, David S; Meissner, Christopher M; Novy, Dennis (American Economic Review, 2008)
What has driven trade booms and trade busts in the past century and a half? Was it changes in global output or in the costs of international trade? To address this question, we derive a micro-founded measure of aggregate bilateral trade costs based on a standard model of trade in differentiated goods. These trade costs gauge the difference between observed bilateral trade and frictionless trade in terms of an implied markup on retail prices of foreign goods. Thus, we are able to estimate the combined magnitude of tariffs, transportation costs, and all other macroeconomic frictions that impede interna tional trade but that are inherently difficult to observe. We use this measure to examine the growth of global trade between 1870 and 1913, its retreat from 1921 to 1939, and its subsequent rise from 1950 to 2000. We find that trade cost declines explain roughly 55 percent of the pre– World War I trade boom and 33 percent of the post–World War II trade boom, while a precipi tous rise in trade costs explains the entire inter